2021
DOI: 10.3390/antiox10010078
|View full text |Cite
|
Sign up to set email alerts
|

Role of Exendin-4 in Brain Insulin Resistance, Mitochondrial Function, and Neurite Outgrowth in Neurons under Palmitic Acid-Induced Oxidative Stress

Abstract: Glucagon like peptide 1 (GLP-1) is an incretin hormone produced by the gut and brain, and is currently being used as a therapeutic drug for type 2 diabetes and obesity, suggesting that it regulates abnormal appetite patterns, and ameliorates impaired glucose metabolism. Many researchers have demonstrated that GLP-1 agonists and GLP-1 receptor agonists exert neuroprotective effects against brain damage. Palmitic acid (PA) is a saturated fatty acid, and increases the risk of neuroinflammation, lipotoxicity, impa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 81 publications
0
4
0
Order By: Relevance
“…GLP1R agonists such as liraglutide have been found to reduce the level of free radicals by promoting expression of anti-oxidative factors such as superoxide dismutase (SOD) and catalase [72]. Consistent with an antioxidative role of liraglutide in neurons, another GLP1 agonist, Exentin-4, has been found to inhibit the generation of ROS in a neuronal cell line exposed to elevated palmitate [22]. Thus, a possible neuroprotective mechanism of action of liraglutide is the induction of anti-oxidative responses to blunt vicious cycles whereby protein misfolding in the ER increases generation of ROS, further impairing ER proteostasis, calcium handling, and mitochondrial function [77].…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…GLP1R agonists such as liraglutide have been found to reduce the level of free radicals by promoting expression of anti-oxidative factors such as superoxide dismutase (SOD) and catalase [72]. Consistent with an antioxidative role of liraglutide in neurons, another GLP1 agonist, Exentin-4, has been found to inhibit the generation of ROS in a neuronal cell line exposed to elevated palmitate [22]. Thus, a possible neuroprotective mechanism of action of liraglutide is the induction of anti-oxidative responses to blunt vicious cycles whereby protein misfolding in the ER increases generation of ROS, further impairing ER proteostasis, calcium handling, and mitochondrial function [77].…”
Section: Discussionmentioning
confidence: 86%
“…In the hypothalamus of mice exposed to a diet with elevated content of SFA there is, in addition to ER stress, fragmentation of the mitochondrial network in POMC neurons and Sim1 MC4R neurons [7,19,20]. Importantly, experiments using primary cultures show that exposure to elevated palmitate also induces mitochondrial depolarization in dorsal sensory neurons [21], cortical neurons [22], and hypothalamic neurons [7], indicative of direct effects by elevated fat to alter mitochondrial function. Metformin and liraglutide, a glucagon-like peptide 1 receptor (GLP1R) agonist, are the most commonly used drugs to treat obese patients with diabetes mellitus (DM) and pre-diabetes [23,24].…”
Section: Introductionmentioning
confidence: 98%
“…We analyzed the protein-coding potential of candidate circRNAs to confirm the possibility of protein translation ( Figure 6 A). The protein-coding potential of seven circRNAs was confirmed using two prediction tools: CPC 2.0 and CPAT [ 38 , 39 ]. It was confirmed that some circRNAs, except circSnx12 and circUsp3, are highly likely to code proteins.…”
Section: Resultsmentioning
confidence: 99%
“…We used the coding potential calculator 2 (CPC 2.0, accessed on 25 January 2023) and the coding potential assessment tool (CPAT, accessed on 25 January 2023) for the prediction of coding potential for the selected circRNAs [ 38 , 39 ]. To predict circRNA-interacting proteins, we performed the analysis as previously described [ 31 ].…”
Section: Methodsmentioning
confidence: 99%
“…A recent study found that PA could aggravate memory loss and neuroinflammation by stimulating the production of pro-inflammatory cytokines, such as tumor necrosis factor alpha [ 6 ], through the nuclear factor kappa-light-chain-enhancer of activated B cells signaling pathway [ 7 ]. High levels of PA promote cell death, impaired neural differentiation, mitochondrial dysfunction, and abnormal neurite outgrowth [ 8 ]. To overcome the synaptic dysfunction observed in people with obesity, it is essential to study neuronal dysfunction under PA toxicity and identify drugs that can improve it.…”
Section: Introductionmentioning
confidence: 99%